IMPROVING ENGLISH SPEAKING SKILLS THROUGH SCIENTIFIC METHOD ASSISTED GRAPHIC MEDIA (Action Research at SMPN 1 Cikidang Sukabumi) - Eni Mulyani; Ifan Iskandar (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
Abstract The objectives of this study were to find out the effect of implementation of scientific method assisted by graphic media to improve students' English speaking skills. The research used action research design. The subjects were 30 second year eight class students of SMPN 1 Cikidang Sukabumi. Observation, interviews, stionnaires, and documentation were employed to collect the data of the students‟ learning ctivities and speaking tests were conducted to identify students‟ speaking achievement. In the scientific method students carry out observing, asking, trying, reasoning and communicating activities, where these activities can train students to speak English. The implementation of this study by applying the scientific method assisted by graphic media is as much as two cycles. In the pre-action stage there were 2 students with a percentage of learning completeness of 6.7%, after the action applied in the first cycle, as many as 8 students with a percentage of learning completeness 26.7% and English speaking skills of students after the second cycle, as many as 28 students with a percentage of 93.3% learning completeness. So, it can be concluded that the scientific method assisted by graphic media can improve English speaking skills of class VIII H students of SMPN 1 Cikidang Sukabumi. Keyword: scientific method, graphic media, English speaking skill.